Analisa Efek Penggunaan Kolam Perikanan Pada Gedung Tinggi di Indonesia - Purnamasari, Tina; *, Ridwan; Paroipo, Wahyu Trifadil; Hura, Juangga Rizki (CV. SINAR HOWUHOWU, 2024)
The use of fish ponds in tall buildings in Indonesia is increasingly popular along with increasing awareness of the importance of a healthy environment and architectural aesthetics. This study aims to analyze the effects of using fish ponds in tall buildings in Indonesia from various perspectives, including environmental, health and economic. This research uses a literature review method by collecting data from various relevant sources. The analysis results show that fish ponds in tall buildings can provide significant benefits, such as improving air quality, reducing stress, and increasing property value. However, there are also challenges to consider, such as treatment costs and potential health problems